ASSESSING SEVENTH GRADERS' MATHEMATICAL LITERACY IN SOLVING PISA-LIKE TASKS - Dewantara, Andi Harpeni; Zulkardi, Zulkardi; Darmawijoyo, Darmawijoyo (Journal on Mathematics Education, 2015)
ThisÂ  design research type development study aims at producing a set of PISA-like mathematics task which is valid and practical as well as has the potential effects. Then, activation of fundamental mathematical capabilities underlying mathematical process related to the mathematical literacy as the main potential effect of the developed PISA-like tasks would be the focus on this paper. The subject of this study were 28 seven graders of SMP Negeri 1 Palembang involved in field test. Data collecting techniques used were students' test result and interviews. Overall findings indicate that 10 items of PISA-like mathematics task developed potentially promote students' mathematical literacy within three mathematical processes. The result also shows that the highest percentage of students' achievement was on the interpreting tasks (52.55%). While achievement for employ and formulate tasks were 40.74% and 39.63% respectively.